2012
DOI: 10.3109/02652048.2012.714410
|View full text |Cite
|
Sign up to set email alerts
|

Improved antifungal activity of itraconazole-loaded PEG/PLA nanoparticles

Abstract: Poly(ethylene glycol)/polylactic acid (PEG/PLA) nanoparticles (NPs) containing the hydrophobic antifungal itraconazole (ITZ) were developed to provide a controlled release pattern of ITZ as well as to improve its aqueous dispersibility and hence enhance its antifungal action. Two PEG/PLA copolymers (PEGylated PLA polymers) were used in this study; branched PEGylated polymer in which PEG was grafted on PLA backbone at 7% (mol/mol of lactic acid monomer), PEG7%-g-PLA, and multiblock copolymer of PLA and PEG, (PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 48 publications
4
16
0
Order By: Relevance
“…The encapsulation test results obtained in the present study (Table ) showed that the increase in length of PEG chains does not lead to a higher drug loading. In general, the observed ITZ content, reaching the maximum value of 6.48% w/w in the case of the product 11 , are comparable with some recently proposed ITZ encapsulation systems based on poly(ethylene glycol)/poly(lactic acid) (PEG/PLA) nanoparticles and micelles formed by PEGylated bile acids and, therefore, could be considered as being satisfactory for a potentially drug delivery material.…”
Section: Resultssupporting
confidence: 84%
“…The encapsulation test results obtained in the present study (Table ) showed that the increase in length of PEG chains does not lead to a higher drug loading. In general, the observed ITZ content, reaching the maximum value of 6.48% w/w in the case of the product 11 , are comparable with some recently proposed ITZ encapsulation systems based on poly(ethylene glycol)/poly(lactic acid) (PEG/PLA) nanoparticles and micelles formed by PEGylated bile acids and, therefore, could be considered as being satisfactory for a potentially drug delivery material.…”
Section: Resultssupporting
confidence: 84%
“…The results of the in vitro tests performed with the synthesized dendrimers 6 , 25 , 29 , and 30 are shown in Figure A. In general, the drug content observed in the case of the structures 6 , 30 , and 25 is comparable with other recently proposed ITZ encapsulation systems based on PLA‐PEG nanoparticles and PEGylated bile acid micelles . Based on the obtained data, preliminary conclusions about key structural factors responsible for the observed effects could be drawn by comparing such parameters of dendrimers as molecular mass, size, and nature of hydrophilic and hydrophobic segments.…”
Section: Resultssupporting
confidence: 65%
“…Nevertheless, the bioavailability of unformulated crystalline ITZ is extremely low, in particular, due to its very low solubility in water, about 1 ng mL −1 in aqueous solutions at pH from 1 to 13 . To overcome this problem, various drug formulations have been recently developed such as solid solutions in poly(ethylene glycol), mixtures with water‐soluble laponite clay, and phosphoric acid, solid dispersions and hot‐stage extrusions with water‐soluble hydroxypropylmethylcellulose (HPMC), liposomes, as well as solid nanoparticles based on polylactic acid‐poly(ethylene glycol) (PLA‐PEG) polymers, micelles formed by PEGylated bile acids, etc. However, in practice, the number of excipients for encapsulation of ITZ is not so large.…”
Section: Introductionmentioning
confidence: 99%
“…Encapsulation within PLA-PEG has tremendous benefits in vivo including protecting the integrity and activity of biomolecules while augmenting their immune-potentiating effects. This copolymer apparently enhances the therapeutic activity of encapsulated drugs 5,7 and consequently is more commonly used for drug delivery. Conversely, it is not widely exploited for vaccine delivery 8 , in spite of its aforementioned inherent properties, which are desirable for vaccines.…”
Section: Introductionmentioning
confidence: 99%